(3OjhGf GdTQja GdQVis - (3CHh GdMSf eMeO Hf GdMSf Hf ehSi Hf eMeO Hf EHQGgje Hf ehSi Hf LYaQ Hf eMeO Hf Ydj Hf GdMSjf Hf Ydj Hf CHj WGdHs
(3ChdgG (B:s
(3hbGd gPg GdbUjOI LhGHkG Yf bUjOI CQSdgG Edjg HYV CUObGFg QVjfG GdXHG ef YfGb GdXHG hVQH GdWdi ef hUGd GdWdG hde fQV HGdHCS Ohf GdSeGM hdG HGdeMGeO Ohf GdLO s
(3BNQgG (B:s
(3hGdfLe hLg ebHd hGdHOQ eQGAI UOjg Je GdOjhGf GdeHGQc GdeSei HOjhGf GdTQja GdQVi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg eWGdYIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs